(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to investigate the relationship between the frequency of interval training and aerobic endurance among futsal extracurricular students at SMP Negeri 3 Ungaran. A total of 35 male students actively participating in the futsal extracurricular program were selected as research subjects. The frequency of interval training was measured using a questionnaire, while aerobic endurance was assessed through the Multistage Fitness Test (Beep Test). Descriptive statistical analysis showed that the average frequency of interval training was 12.43 sessions with an average Beep Test score of 7.51. The normality test indicated that the data were partially non-normal; therefore, Spearman’s rho correlation analysis was used. The results revealed a strong, positive, and statistically significant relationship between the frequency of interval training and aerobic endurance (r = 0.731, p < 0.001). These findings indicate that students who engage more frequently in interval training tend to have better aerobic endurance. This study highlights the importance of incorporating regular interval training sessions in school-based sports programs to enhance physical fitness and athletic performance in futsal.